The survival mechanism of Home Industries (UMKM) of poor families after a disaster - Udji Asiyah (Faculty of Social and Political Science, Universitas Airlangga, 2018)
The numerous forms of dependent UMKMs actors and their financial deficit, as well as the threat of poverty, should be prevented by using the substitute institutions that will be able to fulfill the needs of UMKMs in terms of capital, fulfilment of raw materials and marketing activities. The flood of Bengawan Solo River is often served as an annual problem faced by the UMKM in the disaster prone areas. The aim of this research is to formulate contextual intervention policies and programs, especially for community empowerment of home industries (UMKM) actors who are the disasters victims. This research used quantitative method. The data collection technique is interview with the total number of respondents 100 poor families who rely on their daily lives from business industries (UMKM) and in-depth interview to the ten selected informants. Among the UMKM actors who are looking for capital loans for new business start-up, seems to be the most common way to survive. When the prospect to expand the business is believed to be still there, then a respondent will try to rebuild his business from the bottom. However, when they feel there is no opportunity to restart their businesses, then the mechanism is trying to find another job to survive the survival of his family. The efforts to empower UMKM in disaster prone areas cannot be done by relying on a charitable programs and activities, but most importantly is how to awaken, give opportunities and empower UMKM actors in the real sense.